2021
DOI: 10.1111/pan.14346
|View full text |Cite
|
Sign up to set email alerts
|

Central venous catheter‐related thrombosis in pediatric surgical patients: A prospective observational study

Abstract: Background: Perioperative central venous catheters are required but may be associated with various complications. Aims:The purpose of our study was to assess the incidence and perioperative risk factors for catheter-related internal jugular vein thrombosis in pediatric surgical patients. Methods: This prospective observational study included children under 6 years of age who were scheduled to undergo central venous catheterization of the right internal jugular vein under general anesthesia. A central venous ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 30 publications
(78 reference statements)
0
11
0
Order By: Relevance
“…Several puncture or insertion attempts during CVC placement may also promote thrombosis. 10 Unfortunately, our standard documentation does not provide the number of puncture attempts necessary for the insertion of the CVC. Therefore, based on the available data, no connection can be drawn between repeated punctures and the development of CADVT.…”
Section: Deep Vein Thrombosis Is a Serious Complication In Neonatesmentioning
confidence: 99%
See 2 more Smart Citations
“…Several puncture or insertion attempts during CVC placement may also promote thrombosis. 10 Unfortunately, our standard documentation does not provide the number of puncture attempts necessary for the insertion of the CVC. Therefore, based on the available data, no connection can be drawn between repeated punctures and the development of CADVT.…”
Section: Deep Vein Thrombosis Is a Serious Complication In Neonatesmentioning
confidence: 99%
“…7 Several studies have reported that CADVT occurs in approximately 15%-39% of pediatric patients with a CVC and the risk is particularly high in preterm infants and neonates. 9,10 It must be noted, that the inflammatory and immunosuppressive effects of cardiopulmonary bypass and major surgery may have a different impact on the occurrence of complications in such patients when compared with other conditions. 5,6 Furthermore, the question of the influence of the puncture site of a CVC on the development of CADVT for pediatric cardiac surgery patients has not been conclusively answered in studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Central venous catheter (CVC) placement and ICU admission are the two most important risk factors for VTE in children [2]. Critically ill children are reported to develop CVC-associated DVT (CADVT) at rates of 2–39%, depending on the presence of symptoms and screening techniques [3,4,5 ▪ ,6,7 ▪ ]. CADVT can lead to pulmonary embolism, potentially prolonging duration of mechanical ventilation [8].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have focused on peripheral central catheter-related thrombus, not central catheter-related thrombus (20)(21)(22). At present, the risk factors for CVC-CRT in hospitalized children are still not well identified (16,23), and there is no consensus on the risk factors for CRT in children.…”
Section: Introductionmentioning
confidence: 99%